The effect of vitamin D administration on the clinical and laboratory symptoms of adolescents suffering from polycystic ovary syndrome with vitamin D deficiency - Adeleh Hajizadeh; majid Mirmohammadkhani; Mozhgan Rahmanian (Mashhad University of Medical Sciences, 2023)
Introduction: Since conflicting results have been reported about the relationship between the level of vitamin D in people with polycystic ovary syndrome and related metabolic disorders, the present study was performed with aim to determine the effect of vitamin D administration on the clinical and laboratory symptoms of adolescents with polycystic ovary syndrome with vitamin D deficiency.Methods: This double-blind randomized controlled clinical trial study was performed on 50 patients with sonographic evidence of polycystic ovary syndrome with vitamin D deficiency in two control and intervention groups. The intervention group was given vitamin D and the control group was given placebo. Clinical, laboratory and sonographic symptoms before and after the intervention were compared in two groups. Data were analyzed by SPSS software (version 16), Man-Whitney U and Wilcoxon test. P<0.05 was considered statistically significant.Results: The intervention improved the level of vitamin D in the case group (P<0.001). There was significant difference between the case and control groups in terms of fasting insulin level (P=0.001), serum testosterone level (P<0.001), free testosterone level (P=0.042), LH to FSH ratio (P<0.001), LH level (P<0.001), diastolic blood pressure (P=0.027), and severity of hirsutism (P=0.016). Polycystic ovary syndrome and Oligomenorrhea was more in the control group (P <0.01); However, there was no significant difference between the two groups in terms of fasting blood sugar, triglycerides, HDL, systolic blood pressure, acne severity, and ovarian volume (P>0.05).Conclusion: Considering the role of vitamin D in ovum development and its relationship with the reduction and regulation of insulin, the use of this supplement is recommended to improve the clinical and laboratory symptoms of polycystic ovary syndrome and subsequently correct menstrual disorders and hyperandrogenism. Also, in this study, vitamin D consumption did not cause a significant difference in insulin resistance between the two groups after the intervention.